Use of Information and Communication Technologies in Education : Effectively Integrating Technology in Under-Resourced Education Systems - Vivek, Kumar; Bhattacharjee, Pradyumna (World Bank, Washington, DC, 2021)
Education systems in under-resourced environments face several challenges, some of them exacerbated by the COVID-19 pandemic. A possible way to address some of the challenges is to apply information and communication technologies. However, effectively integrating technology into education systems is a complex task. In this paper, factors contributing to successful integration of technology in education are explored, with a focus on under-resourced contexts. Case studies of successful technology implementation in education systems are discussed and analyzed to identify the factors that drive success. The analysis is framed using the reform strategy offered by The World Development Report 2018 (Learning to Realize Education’s Promise). This is expected to provide policymakers and practitioners a way to align their education technology initiatives and strategies with the larger education reform agenda. Key lessons identified from the analysis are as follows. First, it is necessary to articulate what precisely does the technology intervention change/enable. Second, it is important to better understand the context to develop technologies and implementation strategies that fit the operating context. Third, it is essential to regularly monitor and evaluate programs and to feed that information into continuously improving design and implementation. Fourth, through the entire cycle of technology implementation, stakeholders must be consulted, understood, and empowered. However small the intervention, realizing the potential of technology tools in education requires keeping in mind the big picture offered by these lessons.